Perlindungan Hukum Konsumen Pada Produk Asuransi Online Di Indonesia Pada Era Indusri 4.0 - M.Bagas Hutama P; Arief Suryono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Customers who enter into insurance agreements online receive legal protection based on Law no. 40 of 2014, Consumer Protection Law, Civil Code, KUHD, and Law no. 11 of 2008 concerning Information and Electronic Transactions. Thus, an online insurance policy is recognized as a legally valid electronic document, both in digital and printed form. OJK is responsible for insurance supervision, both online and offline, with a focus on aspects of governance, business ethics and financial health. This supervision includes analysis of reports, examinations and investigations, which are part of the OJK's duties in regulating and supervising the financial services sector in Indonesia.